Gold-nanofève surface-enhanced Raman spectroscopy visualizes hypotaurine as a robust anti-oxidant consumed in cancer survival - Megumi Shiota (Nature Portfolio, 2018)
Surface-enhanced Raman spectroscopy (SERS) visualizes fingerprints of intermolecular vibrations of many metabolites. Here the authors report a SERS imaging technique that enables the visualization of metabolites distribution and automated extraction of tumour boundaries in frozen tissues.